Effect of freeze and thaw cycle and incubation period on the solubilisation of inclusion body protein - Nursyahira, Mohd Rafi (2017)
Overexpression of recombinant protein in bacteria result in the formation of inactive protein. These inactive proteins associate forming insoluble protein aggregates which is referring to inclusion bodies (IBs). Generally, IBs are pure and the aggregated protein inside it has native-like secondary structure which is a bioactive protein. To recover the insoluble and active protein is a major problem encountered. Solubilisation does play a crucial role by unfolded the protein and thus help it to refold properly so that functional bioactive protein can be recovered. Example of mild solubilisation method using low concentration of urea and combine with freeze and thaw method has been proven to increase the efficiency of the recovering of bioactive protein. For freeze and thaw process there are factors that affect the overall process which are freezing incubation period and number of process cycle. Incubation period affect the process by determining the amount of stress needed to be applied so that unfolding process can occur. Number of cycle does affect the protein stability in terms of the occurrence of protein degradation probability. Thus the objective of this research is to investigate effect of freeze and thaw cycle an incubation period on the solubilisation of IBs. For incubation period the experiment was conducted between 1 to 4 days whereas for freeze and thaw cycle experiment conducted between cycle 1 to 4. Moreover, the performance of these two parameters were analysed using native-polyacrylamide gel electrophoresis (n-PAGE) to determine the functional for enhance green fluorescent protein (EGFP) amount and Bradford assay to determine the total protein amount. In this study, incubation period did affected the performance of solubilisation rate in which the IBs being solubilised and then proceed for refolding process and has been proven achieved active form of EGFP. For number of process cycle, it did not affect the solubilisation rate on determining the amount of functional EGFP recovered.